2011
DOI: 10.1007/s10342-011-0541-1
|View full text |Cite
|
Sign up to set email alerts
|

Norway spruce (Picea abies L.) regeneration and growth of understory trees under single-tree selection silviculture in Finland

Abstract: This study presents empirical data on regeneration and growth of understory trees and constructs simple models for predicting these characteristics at various stand structure and post-thinning standing volume levels. The field experiment was established on a grass/herb mineral soil site in central Finland. Regeneration and understory tree growth data were collected from 24 Norway spruce (Picea abies L.)-dominated mixed substands. Seedlings with heights from 5 to 130 cm were measured in 1996 and 2007. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 27 publications
1
12
1
Order By: Relevance
“…However, after harvest, the height growth rates became more similar. The annual height growth rates of the spruce seedlings were in line with comparable studies in Norway, Estonia, and Finland (Granhus 2001;Metslaid et al 2005;Eerikäinen et al 2014), but substantial increases may be expected in the future according to findings by Granhus et al (2008), Lin et al (2012), and Eerikäinen et al (2014), which included longer observation periods. For the first 5 years, the observed height growth of seedlings in this study was also within the range reported for regeneration under shelterwood in southern Sweden by Örlander and Karlsson (2000), Nilsson et al 2002, andNilsson et al (2006).…”
Section: Canopy Gaps and Stand Regenerationsupporting
confidence: 74%
“…However, after harvest, the height growth rates became more similar. The annual height growth rates of the spruce seedlings were in line with comparable studies in Norway, Estonia, and Finland (Granhus 2001;Metslaid et al 2005;Eerikäinen et al 2014), but substantial increases may be expected in the future according to findings by Granhus et al (2008), Lin et al (2012), and Eerikäinen et al (2014), which included longer observation periods. For the first 5 years, the observed height growth of seedlings in this study was also within the range reported for regeneration under shelterwood in southern Sweden by Örlander and Karlsson (2000), Nilsson et al 2002, andNilsson et al (2006).…”
Section: Canopy Gaps and Stand Regenerationsupporting
confidence: 74%
“…However, the absolute height growth of all seedlings was less than previously reported for advanced regeneration under shelterwood and in stands under transformation towards more heterogeneous stand structure [10,13,14,51]. On the other hand, the magnitude was larger than observed for newly established seedlings under shelterwood [8,9] and in boreal Norway spruce single-tree selection stands [4,5,53].…”
Section: Seedling Height Growthcontrasting
confidence: 39%
“…Area-wide measures of canopy structure sampled at the stand or plot have been used to predict seedling growth (Brandeis et al 2001;Chrimes and Nilson 2005;Lin et al 2012). Other research has predicted growth using point-based metrics of canopy structure observed at each seedling (Jain et al 2004;Krueger et al 2007).…”
Section: Discussionmentioning
confidence: 99%